Respon Pertumbuhan Tanaman Pakcoy (Brassica rapa L) dengan Pemberian Teh Kompos Bulu Ayam pada Sistem Hidroponik: Respon Pertumbuhan Tanaman Pakcoy (Brassica rapa L) dengan Pemberian Teh Kompos Bulu Ayam pada Sistem Hidroponik - Alfi Rianti; Riwan Kusmiadi; Rion Apriyadi (Universitas Bangka Belitung, 2019)
Wick system is one of hydroponics system that uses wick asnutrient absorbing media. Chicken feather liquid compost can be used as a substitute for conventional nutrition in pakcoy plant cultivation using hydroponics. This study aims to determine the effect of chicken feather liquid compost and determine the best concentration chicken feather liquid compost on the growth of pakcoy, and to find out the potential of chicken feather liquid compost to replace conventional nutrient solutions in a hydroponic system. This study used completely randomized design (CRD), there were 6 level of treatments which were chicken feather liquid compost concentrations consisting of E0 (1000 ppm Ab-mix), E1 (900 ppm liquid compost ), E2 (800 ppm liquid compost), E3 (700 ppm of liquid compost), E4 (600 ppm of liquid compost), E5 (500 ppm of liquid compost) with 3 replications. The variables observed were plant height, leaf number, leaf color, wet weight and dry weight of plants. The results showed that the nutritional treatment of chicken feather liquid compost had a very significant effect compared to AB-mix, which showed that Ab-mix was superior to the observed variables,ncluding plant height, the number of leaves, leaf colour, wet weight and dry weight of plants. At the first and second week, pakcoy growth was still relatively similar to Ab-mix application. All treatments using compost chicken feather liquid compost could not replace AB-mix nutrient.